Pojavnost depresij v poporodnem obdobju v slovenskem vzorcu - Koprivnik, Petra (Medicinski razgledi, 2005)
Postpartum depression largely develops during the first six months following delivery. Its world-wide prevalence is between 3 and 33%, depending on the diagnostic methods and criteria. An attempt was made to standardize the Edinburgh questionnaire in Slovenia and use it to acquire normative data on the Slovene incidence of postpartum depression. With regard to similar studiescarried out in Israel and in Slovenia using the BDI questionnaire, the incidence of postpartum depression in Slovenia was expected to reach approximately 20%. This prospective research included new mothers whose babieswere delivered at the Ljubljana Maternity Hospital during randomly selected weeks. The EPDS questionnaire was translated. Six weeks after delivery, each of the new mothers received the EPDS questionnaire with an addressed return envelope. The data were processed using statistical software.A total of 449 new mothers were included as respondents; 28 new mothers declined participation or were excluded for not meeting the requirements, and 336 responses were evaluated. Using the EPDS, 21.3% of the new mothers had a score of 10 or higher. In accordance with the established screening criteria, the majority of postpartum depression cases were thought to be included. 10.1% of the new mothers had a score of 13 or higher; this group was thought to include the majority of more severe cases of postpartum depression. The findings confirmed our hypothesis. The incidence of postpartumdepression in Slovenia is 21.3%.
Keywords: Depresivna motnja; Puerperal Disorders; Depressive Disorder; Poporodno obdobje, motnje; ankete; Questionnaires; depresija (medicina); poporodno obdobje; poporodna depresija; epidemiologija